Pengaruh Current Ratio (CR) Dan Debt To Asset Ratio (DAR) Terhadap Return On Asset (ROA) - Cindy Febrianti; Sri Suartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
One way to look at a company's financial health is by using financial ratios. This study aims to determine and analyze the effect of Current Ratio (CR), Dept to Asset Ratio (DAR) on Return On Assets (ROA). The research population used is all plastic and packaging companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. The research sample consisted of 9 companies selected using purposive sampling method from 14 companies obtained from the website of the Indonesia Stock Exchange (BEI) and the sites of the sample companies. The hypothesis testing method used is multiple linear regression analysis. The results showed that Current Ratio (CR) has an effect on Return On Assets (ROA). And Dept to Asset Ratio (DAR) has no effect on Return On Assets (ROA). Keywords: Current Ratio, Debt to Assets Ratio, Asset Returns